USE OF COMBINATIONS FAD AND VERTICAL BAIT ATTRACTORS ON BAGAN FLOATING LIFT CATCHES - Zulkarnain; Simbolon, Domu; Hidayani, Putri Azzahra; Astarini, Julia Eka; Yuwandana, Dwi Putra (Departemen PSP IPB, 2025)
In an effort to improve the function of lights in attracting and collecting fish to be more effective, fishing auxiliary in the form of fish aggregating device attractors made from coconut leaves and nets and vertical bait made from tembang fish and squid solution are used in bagan floating liftnet fishing gear. In addition to the composition of the catch, hauling frequency, catch productivity and the effect of the combination of fish aggregating device attractor and vertical bait compared to the control on the floating net are the objectives of this study. Experimental fishing method has been conducted for 20 trips. The results showed that there was a significant difference between the total catch of the treatment and control floating nets, which were 964.2 kg and 445.4 kg respectively, while the average catch was 48.2 kg/trip and 22.2 kg/trip respectively. The catches are pelagic and demersal fish species dominated by the semar fish (Mene maculata), tembang (Sardinella gibbosa), pepetek (Leiognathus equulus), anchovies (Stelephorus sp.), and squid (Loligo sp.). The use of fish aggregating device attractors and vertical bait resulted in a greater number of settings/hauls compared to the control bagan floating lift net, namely 117 hauls and 90 haul respectively, while increasing the production margin of the catch from the treatment bagan floating lift net compared to the control by 116.5%. Key words: bagan floating lift net, FADs attractor, vertical bait